BIOCERAMIC-BASED ROOT CANAL SEALERS - USE IN ENDODONTICS - L Somolová; Z Zapletalová; M Rosa; Ľ Harvan; I Voborná; Y Morozova (Czech Dental Chamber, 2021)
Introduction and aim: Calcium silicate-based sealers, also referred to as bioceramic-based sealers, can, thanks to their properties, ensure hermetic sealing of root canals in endodontics. The recommended single-cone hydraulic cold obturation method or possibly the method of cold lateral condensation of gutta-percha seems to be a suitable way of using this type of sealers in endodontic obturation. With the correct selection of the main gutta-percha cone, which corresponds exactly to the apical dimension after the root canal has been instrumented, reliable sealing can be achieved in conjunction with a sealer applied as a filler. Due to the high degree of biocompatibility, the possible extrusion of the material into the periodontal tissues does not cause any or only a  small postoperative sensitivity. Bioceramic-based root canal sealers have the ability to fill in the anatomical irregularities of the root canal, or to seal iatrogenic defects. The minimal necessary preparation of coronary dentin, chemical bonding to dentin and relatively low condensation pressure when filling the root canal contribute to reducing the risk of root fracture. Filling the root canals with this group of seals provides, according to the available information, at least comparable results as the gold standard in endodontics - obturation by the method of lateral condensation of gutta-percha.For post-endodontic treatment, it is recommended to perform the final filling therapy at the same visit, preferably using adhesive filling materials. An important point is the separation of the bioceramic sealer, which is hydrophilic in nature, from the adhesive materials, which are hydrophobic. In practice, it is recommended to use a  small amount of hot gutta-percha or glass ionomer cement as such a  spacer. Depending on the clinical situation, FRC posts introduced at the same visit or a subsequent prosthetic solution can also be used for postendodontic reconstruction.Secondary endodontic treatment is possible with the use of bioceramic-based sealers, but the removal of material that has a chemical bond to the walls of the root canal is difficult and belongs more to the hands of an endodontic specialist.Conclusion: By simplifying the work procedure, bioceramic-based sealers can contribute to the improvement of obturation in a general dentist's office. However, they can also be of benefit to the work of an endodontic specialist not only in solving complicated cases. However, further research is needed to finally evaluate this type of sealer in endodontic field.